Two-photon absorption processes in semiconductor quantum dots - López Gondar,J. (2006)
The two-photon absorption process is a nonlinear phenomenon that shows very low optical efficiency in bulk semiconductors. For this reason the detection of these processes becomes very difficult from the experimental point of view. Nevertheless, when dealing with semiconductor QD's with few nanometer radii, these transitions are enhanced and the detection is possible. In this contribution we present analytical calculations for the absorption coefficient in CdSe spherical QD's subjected to these second order processes, as a function of the characteristic dot parameters. The intensities of the absorption peaks, as well as the statistical treatment involving QD's ensembles, are also reported.